IMPACT OF STRESS ON JOB PERFORMANCE OF POLICE PERSONNEL - A STUDY OF AJMER DISTRICT (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In recent years, stress has increased in many areas of life, but especially at work. The prevalence of stress in workplaces has significant practical and financial repercussions. To investigate the connection between workplace stress and performance, numerous studies have been carried out. Job performance can be defined as a procedure in which a person, according to the usual limits of reasonable usage of the assets that are accessible, is able to do the task given to them or them satisfactorily. In order to conduct the study, 73 police personnel from the Ajmer district were chosen at random. The right information was gathered utilizing a standardized questionnaire.The hypothesis was examined using the linear regress test. The results demonstrated that occupational stress had a negative impact on police officers' performance. Resulting in feel upset, feel difficulty and feeling of irritation. The outcome also demonstrates that most of the police officers in the Ajmer district experience reduced workplace stress.